Sanctuary cinema : origins of the Christian film industry - Lindvall, Terry (New York University Press, 2007)
Sanctuary Cinema provides the first history of the origins of the Christian film industry. Focusing on the early days of film during the silent era, it traces the ways in which the Church came to adopt film making as a way of conveying the Christian message to adherents. Surprisingly, rather than separating themselves from Hollywood or the American entertainment culture, early Christian film makers embraced Hollywood cinematic techniques and often populated their films with attractive actors and actresses. But they communicated their sectarian message effectively to believers, and helped to shape subsequent understandings of the Gospel message, which had historically been almost exclusively verbal, not communicated through visual media. -- PUBLISHER'S DESCRIPTION.